1989
DOI: 10.1099/00222615-30-2-137
|View full text |Cite
|
Sign up to set email alerts
|

Mutation induced by vibriophage PS166 infection changes biotype and phage type of Vibrio cholerae

Abstract: Summary. The effect of a newly isolated vibriophage, PS166, on Vibrio cholerae (El Tor) MAK757 was investigated. Two PS166-resistant mutants of strain MAK757 were isolated. These had undergone transition to the classical biotype with concomitant acquisition of new phage sensitivity. However, the parental Ogawa serotype remained unchanged. These mutant strains also showed a unique temperate phage-sensitivity profile, distinct from that of strain MAK757. The possible target of phage PS166 interaction is discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…With a V. cholerae genomic microarray that displayed more than 93% of the predicted genes of the whole genome sequence of El Tor strain N16961, Dziejman et al (9) showed that only seven genes were absent solely in classical strains but present in other strains, leading them to speculate that classical biotype strains may be derived from a primordial environmental strain that was more El Tor like than previously thought. Mitra et al have previously reported the involvement of bacteriophage PS166 in the acquisition of some classical biotypespecific properties by El Tor strains (22,23). Insertion of lysogenic phage genomes in the bacterial chromosome leading to the activation or inactivation of certain genes or expression of new phage-encoded genes is a natural phenomenon in the origination of genetic diversity.…”
Section: Discussionmentioning
confidence: 99%
“…With a V. cholerae genomic microarray that displayed more than 93% of the predicted genes of the whole genome sequence of El Tor strain N16961, Dziejman et al (9) showed that only seven genes were absent solely in classical strains but present in other strains, leading them to speculate that classical biotype strains may be derived from a primordial environmental strain that was more El Tor like than previously thought. Mitra et al have previously reported the involvement of bacteriophage PS166 in the acquisition of some classical biotypespecific properties by El Tor strains (22,23). Insertion of lysogenic phage genomes in the bacterial chromosome leading to the activation or inactivation of certain genes or expression of new phage-encoded genes is a natural phenomenon in the origination of genetic diversity.…”
Section: Discussionmentioning
confidence: 99%
“…The infection of V. eltor MAK757 cells with phage PS166 produced plaques with resistant growth in their centers. Some of these resistant colonies were found to exhibit properties of the classical biotype, indicating phage conversion (Mitra, 1989). This resistant growth could be due to a phage receptor mutation or to a phage-immune strain due to lysogenization with phage PS166.…”
Section: Lysogeny Of Phage Ps166 In V Eltor Mak757 Cellsmentioning
confidence: 99%
“…It was proposed that the pandemic strain of one biotype might arise from other biotypes of cholera Vibrio by transduction with a temperate phage or by mutation (Ogg et al, 1978). Earlier, we identified phage PS166, which could convert V. eltor MAK757, serotype Ogawa strains to the classical biotype (Mitra, 1989). However, the phage was not characterized, and the molecular mechanism behind the reported biotype conversion was not known.…”
Section: Introductionmentioning
confidence: 96%
“…Historically, a major emphasis was placed on phage typing of V. cholerae (Basu and Mukerjee, 1968;Chattopadhyay et al ., 1993) and phage therapy was proposed for treatment of cholera in the early years of cholera research. Subsequent studies showed that temperate bacteriophages play a role in the lytic sensitivity and serotype conversion of Vibrio cholerae (Siddiqui and Bhattacharyya, 1982;Mitra, 1989). Recently, there has been renewed interest in V. cholerae phages because of their role in lateral transfer of genes in the environment and emergence of toxigenic strains.…”
Section: Introductionmentioning
confidence: 99%